BABY BLUES SYNDROME AND LEVELS OF HOUSEHOLD HARMONY: ISLAMIC FAMILY LAW CONCEPT - Asmita, Sri; Fathimah, Ema; Syarudin, Ahmad Zazili (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The trauma experienced by women after childbirth often leads to baby blues syndrome, which shows that the shock after childbirth can affect the physical and psychological changes of a woman. This paper aims to examine and analyse the phenomenon of baby blues syndrome experienced by postpartum women, which can affect family harmony and resilience, especially in the concept of Islamic family law. The study in this paper is descriptive qualitative. The data is collected through a library research approach and through the process of reading and searching on the Google search engine with the keywords